A influência da irrigação peritonel de clohexidina ou de solução salina na cicatrização do cólon de ratos com peritonite - Paulo Roberto Rodrigues Bicalho (2009)
Background: Chlorhexidine is an antiseptic that has a broad spectrum of activity and low toxicity profile, at therapeutic concentrations, in both animal models of peritonitis and clinical setting. Some animal studies, the delaying effect of intraperitoneal sepsis on the healing of colonic anastomoses has been shown. This study aimed to investigate the effects of Chlorhexidine on the healing of colonic anastomoses in thepresence of polymicrobial sepsis. Methods: intra-abdominal infection was produced in 16 rats by the cecal ligation and puncture technique (CLP), at control grup no infection was made. After 2 hours, the animals underwent relaparotomy and divided into 3 groups: control (cecalmobilization and anastomosis, group A, n 08); Saline (Intra-abdominal infection, anastomosis and saline solution lavage, group B, n 08); and Chlorhexidine (Intraabdominal infection, anastomosis and chlorhexidine lavage, group C, n 08). The rats were killed on 7th postoperative day, harvested peritoneal biopsies and resected colon containing anastomosis to measure the bursting pressure and examined theresected specimens histologically. Results: no difference in mortality was found (p = 0.27). The incidence of adhesions was 1.6 ± 0.9, 1.1 ± 0.4 and 1.8 ± 0.8 in groups A, B and C respectively, however, they were strong in all cases (100%) in the group treated with chlorhexidine. The average of peritoneal inflammation degree was 2.75 ± 1.03 in group A; 2.43 ± 1.13 ingroup B; and 0.83 ± 0.75 in group C (p = 0.01). The bursting pressures was also lower in animals of group C (156.7 ± 53.2) than that treated with saline (208.6 ± 72.7) and control (196.3 ± 49.8), p = 0.06. Conclusions: the visceral peritoneum inflammation was lower in animals treatedwith chlorhexidine than those of saline group.